Sheet-type insulating varnish and its manufacturing method, electrical equipment, and rotating electrical machine

JP7642153B2Active Publication Date: 2025-03-07MITSUBISHI ELECTRIC CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024502317
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-02-24
Publication Date
2025-03-07
Estimated Expiration
2042-02-24

AI Technical Summary

Benefits of technology

【0011】 本願に開示されるシート型絶縁ワニスによれば、加熱時に熱硬化性樹脂が流動して絶縁対象となる部材の隙間の細部に浸透し、この隙間を確実に埋め、硬化後に絶縁性、機械強度、放熱性に優れた特性を有するシート型絶縁ワニスを提供することができる。 本願に開示されるシート型絶縁ワニスの製造方法によれば、加熱時に熱硬化性樹脂が流動して絶縁対象となる部材の隙間の細部に浸透し、この隙間を確実に埋め、硬化後に絶縁性、機械強度、放熱性に優れた特性を有するシート型絶縁ワニスを得ることができる。 本願に開示される電気機器によれば、加熱時に熱硬化性樹脂が流動して絶縁対象となる部材の隙間の細部に浸透し、この隙間を確実に埋め、硬化後に絶縁性、機械強度、放熱性に優れた特性を有するシート型絶縁ワニスを適用した電気機器を提供することができる。 本願に開示される回転電機によれば、加熱時に熱硬化性樹脂が流動して絶縁対象となる部材の隙間の細部に浸透し、この隙間を確実に埋め、硬化後に絶縁性、機械強度、放熱性に優れた特性を有するシート型絶縁ワニスを適用した回転電機を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007642153000005
    Figure 0007642153000005
  • Figure 0007642153000006
    Figure 0007642153000006
  • Figure 0007642153000007
    Figure 0007642153000007
Patent Text Reader

Abstract

A sheet-type insulating varnish (1) to be arranged in a gap between members to be insulated is obtained by forming a thermosetting resin composition into a sheet shape in an uncured or semi-cured state, the thermosetting resin composition comprising: a first thermosetting resin that is a solid at normal temperature; a second thermosetting resin that is a liquid at normal temperature; a latent curing agent that is reactively inactive at 60ºC or lower; and thermally expandable microcapsules (3) that have a maximum particle size that is smaller than the dimensions of the gap, have an average particle size that is smaller than 0.5 times the dimensions of the gap, and have a foaming start temperature of 60ºC or higher, with the thermosetting resin composition containing 10-90 parts by mass of the first thermosetting resin per 100 parts by mass of the total of the first thermosetting resin and the second thermosetting resin.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present application relates to a sheet-type insulating varnish, a manufacturing method thereof, an electric device, and a rotating electric machine. [Background technology]

[0002] In the field of electrical equipment including electronic devices equipped with semiconductor modules, power modules, power supply devices, etc., and in the field of rotating electrical machines including electric motors, generators, compressors, etc., there is an increasing demand for insulation and heat dissipation due to miniaturization and higher output. For this reason, insulating materials disposed in the gaps between members constituting electrical equipment and rotating electrical machines are required to have high insulation properties and heat dissipation properties. In electrical equipment, insulating materials are placed in the gap between heat-generating components such as semiconductor chips, diodes, or transformer coils and the board, or between the board and the housing. When insulating materials are placed in such gaps between components, partial air spaces remaining can cause a decrease in insulation, heat dissipation, and vibration resistance. The problem of heat dissipation is particularly serious in space equipment used in a vacuum with zero thermal conductivity.

[0003] The rotating electric machine includes a rotor, a stator core, and a stator having a stator coil. Rotating electric machines are becoming smaller and more powerful. Rotating electric machines include an insulating member inside, and as rotating electric machines become smaller and more powerful, insulating materials used for the insulating member are required to have excellent insulation properties, heat resistance, and heat dissipation properties. When an insulating member is disposed between members to be insulated in a rotating electric machine, for example, in a gap between a stator core and a stator coil, if an air layer is partially left in the gap, this causes a decrease in insulation properties, heat dissipation properties, and vibration resistance. When the stator coil is housed in the slot of the stator core, insulating paper is inserted into the gap between the inner wall of the slot and the stator coil, and the stator coil is impregnated with liquid insulating varnish.

[0004] However, as the space factor of the stator coil increases, the gaps between the inner wall of the slot, the stator coil, and the insulating paper, as well as the gaps within the stator coil, become narrower, which causes a problem that the insulating varnish does not sufficiently penetrate the stator coil, resulting in partial adhesion. In addition, when a low-viscosity insulating varnish is used to increase the permeability, much of the varnish dripped onto the coil end leaks out onto the end face of the iron core, resulting in an insufficient amount of varnish adhering to the inside of the stator coil. As a result, if the adhesion performance of the stator coil is reduced, it will have a negative impact on the long-term insulation reliability of the rotating electric machine. In particular, in the case of rotating electric machines for automobiles, a reduction in the adhesion performance of the stator coil is a factor that deteriorates the noise, vibration, and harshness (hereinafter referred to as NVH characteristics), which are one of the standards for estimating the comfort of an automobile.

[0005] In addition, since the heat generation temperature of the stator coil is on the rise with the increase in output, it is necessary to improve the heat dissipation performance of the stator coil from the viewpoint of the durability of the rotating electric machine. However, if the insulating varnish is not sufficiently adhered to the stator coil and an air gap exists between the stator coil and the stator core, the problem arises that the heat of the stator coil cannot be efficiently dissipated to the stator core.

[0006] In order to solve these problems caused by insulating varnish, a method has been disclosed in which the stator coil is fixed to the stator core in an insulated manner without impregnating the stator coil with insulating varnish (for example, Patent Document 1). Also disclosed is a method of filling the gap between the stator coil and the stator core with an adhesive sheet having an expandable adhesive layer that foams and hardens in a short period of time (for example, Patent Document 2). [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Patent Publication No. 2021-70748 [Patent Document 2] International Publication No. WO2016 / 163514 Summary of the Invention [Problem to be solved by the invention]

[0008] The surface of a substrate on which electronic components are mounted in an electronic device, and the surface of an iron core and coil made of laminated electromagnetic steel plates for a rotating electric machine have unevenness. The thermosetting resin composition for sheet-type insulating varnish in Patent Document 1 is compressed to a predetermined thickness by pressure at room temperature, and flows and penetrates into the fine spaces between components by heating during curing, so that the gaps between the components to be insulated can be reliably filled, and the two can be insulated and fixed together. However, when the unevenness is large and when the varnish layer has high thermal fluidity, there is a problem that voids are generated partially, which reduces the cooling performance and insulation performance. On the other hand, in Patent Document 2, an adhesive sheet is attached to one of the substrates and expands when heated to fill the gap, but it does not flow into the gap of the coil and cannot be fixed, and large voids are formed inside the sheet due to foaming, which may cause partial discharge when voltage is applied, and the sheet layer is fragile and may crack due to vibration. In other words, there is a problem of reducing the insulation, mechanical strength, and heat dissipation of the sheet layer.

[0009] The present application discloses technology for solving the problems described above, and has as its object to provide a sheet-type insulating varnish in which a thermosetting resin flows when heated, penetrating into the fine gaps of the components to be insulated, reliably filling these gaps, and having excellent properties in terms of insulation, mechanical strength, and heat dissipation after hardening, as well as a method for producing the same, and further, an electrical device and a rotating electric machine to which this sheet-type insulating varnish is applied. [Means for solving the problem]

[0010] The sheet-type insulating varnish disclosed in the present application is a sheet-type insulating varnish to be placed in a gap between members to be insulated, and includes a first thermosetting resin that is solid at room temperature, a second thermosetting resin that is liquid at room temperature, a latent curing agent that is inactive at 60°C or less, and thermally expandable microcapsules that have a maximum particle size smaller than the dimension of the gap, an average particle size smaller than 0.5 times the dimension of the gap, and a foaming start temperature of 60°C or more, and a thermosetting resin composition that includes 10 parts by mass to 90 parts by mass of the first thermosetting resin per 100 parts by mass of the total of the first thermosetting resin and the second thermosetting resin is formed into a sheet in an uncured or semi-cured state. and further comprising a curing accelerator, and when the reaction initiation temperature of the latent curing agent is lowered by the curing accelerator, the foaming initiation temperature of the thermally expandable microcapsules is 60°C or higher and is 20°C higher than the reaction initiation temperature of the curing accelerator, and the amount of the thermally expandable microcapsules is 1 to 100% by mass based on the total amount of the first thermosetting resin and the second thermosetting resin. Sheet type insulating varnish. The method for producing a sheet-type insulating varnish disclosed in the present application is a method for producing a sheet-type insulating varnish to be placed in a gap between components to be insulated, the method comprising: a first step of stirring and mixing a thermosetting resin composition, the thermosetting resin composition comprising: a first thermosetting resin that is solid at room temperature; a second thermosetting resin that is liquid at room temperature; a latent curing agent that is inactive at 60°C or less; and thermally expandable microcapsules having a maximum particle size smaller than the dimension of the gap, an average particle size smaller than 0.5 times the dimension of the gap, and a foaming start temperature of 60°C or more; the first thermosetting resin being 10 parts by mass to 90 parts by mass per 100 parts by mass of the first thermosetting resin and the second thermosetting resin; and the thermally expandable microcapsules being 1 to 100 mass% per 100 parts by mass of the first thermosetting resin and the second thermosetting resin; and an organic solvent for dilution to prepare a slurry of the thermosetting resin composition; The method includes a second process in which the slurry is applied to a release film or release paper in a thickness that is 1.1 to 2.0 times the dimension of the gap, and then dried so that the thickness has a compression rate that reduces by 10% or more when a pressure of 25 MPa is applied at room temperature. The electrical device disclosed in the present application comprises a substrate on which electronic components are mounted, and a housing to which the substrate is fixed, and the above-mentioned sheet-type insulating varnish is disposed in either or both of the gaps between the electronic components and the substrate and the gap between the substrate and the housing. The rotating electric machine disclosed in the present application has a stator coil housed in the slot of a stator core, and includes the above-mentioned sheet-type insulating varnish disposed in the gap between the inner wall of the slot and the stator coil. Effect of the Invention

[0011] According to the sheet-type insulating varnish disclosed in the present application, the thermosetting resin flows when heated, penetrating into the fine gaps in the components to be insulated and reliably filling these gaps, and it is possible to provide a sheet-type insulating varnish that has excellent properties in terms of insulation, mechanical strength, and heat dissipation after curing. According to the method for producing a sheet-type insulating varnish disclosed in the present application, when heated, the thermosetting resin flows and penetrates into the fine gaps in the components to be insulated, reliably filling these gaps, thereby obtaining a sheet-type insulating varnish that has excellent properties in terms of insulation, mechanical strength, and heat dissipation after curing. According to the electrical device disclosed in the present application, it is possible to provide an electrical device to which a sheet-type insulating varnish is applied, in which a thermosetting resin flows when heated and penetrates into the fine gaps in the components to be insulated, reliably filling these gaps, and which has excellent properties in terms of insulation, mechanical strength, and heat dissipation after curing. According to the rotating electric machine disclosed in the present application, a rotating electric machine can be provided in which a sheet-type insulating varnish is applied, in which a thermosetting resin flows when heated and penetrates into the fine gaps of the components to be insulated, reliably filling these gaps, and which has excellent properties in terms of insulation, mechanical strength, and heat dissipation after hardening. [Brief description of the drawings]

[0012] [Figure 1] Fig. 1A is a cross-sectional view showing a schematic configuration of a sheet-type insulating varnish according to embodiment 1. Fig. 1B is a cross-sectional view showing a schematic configuration of a sheet-type insulating varnish according to embodiment 1. [Diagram 2] 4 is a cross-sectional view illustrating a change in shape when the sheet-type insulating varnish according to the first embodiment is applied to a rotating electric machine. FIG. [Diagram 3] 10 is a flowchart of a method for producing a sheet-type insulating varnish according to the second embodiment. [Figure 4] FIG. 11 is an explanatory diagram of a case where a sheet-type insulating varnish is applied to a power device according to a fourth embodiment. [Diagram 5] FIG. 13 is a perspective view of a stator of a rotating electric machine according to a fifth embodiment. [Figure 6]FIG. 11 is a cross-sectional view of a stator of a rotating electric machine according to embodiment 5. [Figure 7] FIG. 13 is an explanatory diagram of a case where a sheet-type insulating varnish is applied to a stator of a rotating electric machine according to embodiment 5. [Figure 8] FIG. 13 is an explanatory diagram of a case where a sheet-type insulating varnish is applied to a stator of a rotating electric machine according to embodiment 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Embodiment 1 The first embodiment relates to a sheet-type insulating varnish that includes a first thermosetting resin that is solid at room temperature, a second thermosetting resin that is liquid at room temperature, a thermally expandable microcapsule having a foaming initiation temperature of 60°C or higher, a latent curing agent that is inactive at temperatures below 60°C, and, if necessary, a filler.

[0014] Hereinafter, the sheet-type insulating varnish according to embodiment 1 will be described with reference to Figures 1A and 1B, which are cross-sectional views showing a schematic configuration of the sheet-type insulating varnish, and Figure 2, which is a cross-sectional view explaining the change in shape when the sheet-type insulating varnish is applied to a rotating electric machine.

[0015] First, the schematic configuration and function of the sheet-type insulating varnish will be described with reference to FIGS. 1A, 1B, and 2. FIG. 1A and 1B are cross-sectional views showing a schematic configuration of a sheet-type insulating varnish according to the first embodiment. A sheet-type insulating varnish 1 a in FIG. 1A has a basic structure and contains a resin component 2 and thermally expandable microcapsules 3 . Resin component 2 contains a first thermosetting resin that is solid at room temperature and a second thermosetting resin that is liquid at room temperature, with 10 to 90 parts by mass of the first thermosetting resin per 100 parts by mass of the first thermosetting resin and the second thermosetting resin in total, a latent curing agent that is inactive at 60°C or less, and, as necessary, a curing accelerator, a thermoplastic resin, a film-forming agent, a tackifier, an adhesion promoter, etc. The thermally expandable microcapsules 3 have a maximum particle size smaller than the size of the gap to which they are applied, an average particle size smaller than 0.5 times the size of the gap, and a foaming start temperature of 60° C. or higher. The sheet-type insulating varnish 1a has a basic structure in which thermally expandable microcapsules 3 are dispersed in a resin component 2. In addition, in order to improve the thermal conductivity and mechanical strength and to thicken the sheet-type insulating varnish, the basic structure shown in Fig. 1A may be configured to have inorganic and resin-based fillers 4 dispersed therein, as shown in Fig. 1B. The varnish with the fillers 4 dispersed therein is called sheet-type insulating varnish 1b. In addition, when the sheet-type insulating varnish 1a having the basic structure and the sheet-type insulating varnish 1b having the filler 4 dispersed therein are described together without distinction, they will be described as the sheet-type insulating varnish 1.

[0016] Next, the function of the sheet-type insulating varnish 1 will be described with reference to FIG. Fig. 2 illustrates the change in shape of the sheet-type insulating varnish 1b when the sheet-type insulating varnish 1b is applied to a rotating electric machine. In Fig. 2, a stator coil 21 and a stator core 22 are described as components of the rotating electric machine to which the sheet-type insulating varnish 1b is applied. In FIG. 2, F2a indicates a state in which the sheet-type insulating varnish 1b is inserted between the stator coil 21 and the stator core 22 and fixed to the stator core 22. F2b shows the state where the stator coil 21 is pressed against the sheet-type insulating varnish 1b. An air layer 7 is formed. In the figure, "PJ" stands for "pressure-bonded". F2c shows the penetration and thickening of the varnish layer due to heating. In F2c, the thermally expandable microcapsules 3 after foaming are shown as foamed thermally expandable microcapsules 8. The increase in the varnish layer causes the air layer 7 to disappear. In the figure, "HT" stands for "heating," "VP" for "varnish penetration," "FM" for "foaming," and "HD" for "hardening." As can be seen in Figure 2, the sheet-type insulating varnish 1 is efficiently compressed to a specified thickness when pressurized at room temperature. Furthermore, when heated during curing, it flows and penetrates into the fine spaces between components, after which the varnish layer thickens due to foaming of the thermally expandable microcapsules 3. As a result, air spaces are eliminated and gaps between the components to be applied, i.e., the components to be insulated, are reliably filled, and the two can be insulated and fixed together.

[0017] The thermosetting resin composition, which is the material of the sheet-type insulating varnish 1, will be described. The thermosetting resin composition is a resin composition for the sheet-type insulating varnish that is placed in the gap between the components to be insulated. At least a part of the gap between the components to which the varnish is applied has a substantially constant dimension (hereinafter, this is referred to as the gap dimension). The thermosetting resin composition includes a first thermosetting resin that is solid at room temperature, a second thermosetting resin that is liquid at room temperature, and a latent curing agent that is inactive at 60° C. or less. The thermosetting resin composition further includes thermally expandable microcapsules 3 that have a maximum particle size smaller than the size of the gap, an average particle size smaller than 0.5 times the size of the gap, and a foaming start temperature of 60° C. or more, and 10 to 90 parts by mass of the first thermosetting resin relative to 100 parts by mass of the first and second thermosetting resins in total. Furthermore, the composition further includes inorganic and resin-based fillers, curing accelerators, thermoplastic resins, film-forming agents, tackifiers, and adhesion agents, etc., as necessary. In the following description, when the first thermosetting resin and the second thermosetting resin are not particularly distinguished from each other and both are collectively described, or when a mixed resin of these is described, it is simply described as "thermosetting resin." Furthermore, room temperature refers to 15°C to 35°C.

[0018] The sheet-type insulating varnish 1 produced using a thermosetting resin composition combining the above raw materials has the flexibility to be compressed to a predetermined thickness when pressurized at room temperature, and further has the property of flowing when heated during curing, penetrating into the fine spaces between components, and then thickening the varnish layer due to expansion of the thermally expandable microcapsules 3. Therefore, the thermosetting resin composition according to the first embodiment is suitable for producing the sheet-type insulating varnish 1 that reliably fills the gaps between components to be insulated, insulating and bonding them together.

[0019] The thermosetting resin may be any of known resins such as epoxy resins, phenol resins, unsaturated polyester resins, polyurethane resins, diallyl phthalate resins, and silicone resins. In particular, it is preferable to use at least one of epoxy resins, phenol resins, and unsaturated polyester resins such as vinyl ester resins, which are commonly used as insulating varnishes.

[0020] Specific examples of thermosetting resins include bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol AD ​​type epoxy resins, brominated bisphenol A type epoxy resins, brominated bisphenol F type epoxy resins, brominated bisphenol AD ​​type epoxy resins, alicyclic epoxy resins, brominated alicyclic epoxy resins, phenol novolac type epoxy resins, cresol novolac type epoxy resins, brominated phenol novolac type epoxy resins, brominated cresol novolac type epoxy resins, hydrogenated bisphenol A type epoxy resins, triglycidyl isocyanate, hydantoin type epoxy resins, heterocyclic epoxy resins, biphenyl skeleton-containing aralkyl type epoxy resins, dicyclopentadiene type epoxy resins, novolac type phenolic resins, resol type phenolic resins, epoxy (meth)acrylate resins (vinyl ester type resins), urethane (meth)acrylate resins, polyether (meth)acrylate resins, polyester (meth)acrylate resins, and the like. These resins may be used alone or in combination of two or more.

[0021] The first thermosetting resin is solid at room temperature, and has a melting point or a softening temperature of glass transition point of 160° C. or less, and more preferably 125° C. or less. If the softening temperature is higher than 160° C., the polymerization reaction with the second thermosetting resin does not proceed easily when heated, and the heating temperature in the curing process needs to be higher than 200° C., which is not preferable because it induces deterioration of the components to be insulated.

[0022] In addition, the first thermosetting resin must be soluble in at least one of the liquid second thermosetting resin and the organic solvent for dilution (hereinafter referred to as the diluent). If the first thermosetting resin is not soluble, the resin components will not be uniformly dissolved when the slurry is prepared, and a homogeneous sheet-type insulating varnish 1 cannot be formed.

[0023] Furthermore, when the first thermosetting resin is an epoxy resin, from the viewpoint of increasing the adhesive strength with the member to be insulated, an epoxy resin having an epoxy equivalent of 200 or more and a softening temperature in the range of 50°C to 160°C (hereinafter, when the lower and upper limits of such values ​​or ratios are indicated, it will be written as "50°C to 160°C"). Also, when the first thermosetting resin is an unsaturated polyester resin such as a vinyl ester resin, it is preferable that the softening temperature is 50°C to 160°C. These have excellent workability when premixed with other raw materials at room temperature, and are easily melted by heating, improving the uniform mixing with other raw materials.

[0024] When the first thermosetting resin is an epoxy resin, the second thermosetting resin is preferably an epoxy resin that is liquid at room temperature in order to increase the adhesive strength with the component to be insulated, and more preferably a bisphenol A type epoxy resin or a bisphenol F type epoxy resin in order to increase the dissolving power of the first thermosetting resin. When the first thermosetting resin is an unsaturated polyester resin, the second thermosetting resin is preferably a low-viscosity, low-molecular-weight oligomer or monomer of the unsaturated polyester resin in order to increase the dissolving power of the first thermosetting resin.

[0025] In this way, by using the first and second thermosetting resins which are in different states at room temperature and adjusting the mass ratio, etc., it is possible to control the surface adhesion (tackiness), mechanical strength (toughness), adhesion, fluidity when heated, etc. at room temperature of the sheet-type insulating varnish 1. The first thermosetting resin is 10 parts by mass to 90 parts by mass, more preferably 15 parts by mass to 85 parts by mass, relative to 100 parts by mass of the total of the first and second thermosetting resins.

[0026] In terms of mass ratio, the mass ratio (A / B) of the first thermosetting resin to the second thermosetting resin is preferably in the range of 10 / 90 to 90 / 10. When the mass ratio (A / B) is less than 10 / 90, the amount of liquid resin is large, so that the sheet-type insulating varnish 1 is not stable after drying and cannot be peeled off from the release substrate. When the mass ratio (A / B) is more than 90 / 10, the amount of solid resin is large, so that the toughness (tenacity of the material) of the sheet-type insulating varnish 1 is low. Therefore, cracks and chips are likely to occur during drying or peeling from the release substrate, and workability is poor.

[0027] To produce a highly tough and stable sheet-type insulating varnish 1, the mass ratio (A / B) is preferably in the range of 15 / 85 to 85 / 15. To ensure adhesion that allows easy attachment to components to be insulated, the mass ratio (A / B) is preferably in the range of 15 / 85 to 50 / 50. On the other hand, when adhesion on the surface of the sheet-type insulating varnish 1 is not required (for example, when adhesion deteriorates workability), the mass ratio (A / B) is preferably in the range of 50 / 50 to 85 / 15 in order to reduce surface adhesion.

[0028] The thermosetting resin composition may contain a curing agent for curing the thermosetting resin. The curing agent is not particularly limited, and a known curing agent may be appropriately selected according to the type of the thermosetting resin. The curing agent may be amines, phenols, acid anhydrides, imidazoles, polymercaptan curing agents, polyamide resins, or the like.

[0029] Specific examples of the curing agent include alicyclic acid anhydrides such as methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, and himic anhydride, aliphatic acid anhydrides such as dodecenylsuccinic anhydride, aromatic acid anhydrides such as phthalic anhydride and trimellitic anhydride, aromatic diamines such as dicyandiamide and 4,4'-diaminodiphenylsulfone, organic dihydrazides such as adipic acid dihydrazide, boron halide amine complexes such as boron trifluoride, boron trichloride, and boron tribromide, tris(dimethylamino) methyl)phenol, dimethylbenzylamine, 1,8-diazabicyclo(5,4,0)undecene and its derivatives, imidazoles such as 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, and 1-cyanoethyl-2-methylimidazole, polyhydric phenol compounds such as bisphenol A, bisphenol F, bisphenol S, phenol novolac resin, cresol novolac resin, and p-hydroxystyrene resin, and organic peroxides.

[0030] Representative examples of the boron halide amine complex include boron trifluoride monoethylamine complex, boron trifluoride diethylamine complex, boron trifluoride isopropylamine complex, boron trifluoride chlorophenylamine complex, boron trifluoride-triallylamine complex, boron trifluoride benzylamine complex, boron trifluoride aniline complex, boron trichloride monoethylamine complex, boron trichloride phenol complex, boron trichloride piperidine complex, boron trichloride dimethyl sulfide complex, boron trichloride N,N-dimethyloctylamine complex, boron trichloride N,N-dimethyldodecylamine complex, boron trichloride N,N-diethyldioctylamine complex, etc. These curing agents may be used alone or in combination of two or more.

[0031] The amount of the curing agent may be appropriately adjusted depending on the type of thermosetting resin and curing agent used, and is usually preferably 0.1 to 200 parts by mass per 100 parts by mass of the thermosetting resin.

[0032] Furthermore, when an epoxy resin is used as the thermosetting resin, the curing agent is preferably a latent curing agent that is reactively inactive at 60°C or less from the viewpoints of storage stability, curing property, and cured resin properties of the sheet-type insulating varnish 1. Specific examples of the latent curing agent include boron halide amine complexes such as boron trifluoride-amine complexes, dicyandiamide, organic acid hydrazides, and aromatic diamines such as 4,4'-diaminodiphenylsulfone. These latent curing agents may be used alone or in combination of two or more kinds. The amount of the latent curing agent is preferably 0.3 to 2.0 in terms of the equivalent ratio of the thermosetting resin to the epoxy resin, and more preferably 0.5 to 1.5 from the viewpoint of the stability of the cured product properties.

[0033] In addition, when an unsaturated polyester resin is used as the thermosetting resin, an organic peroxide is used as a reaction initiator to start a polymerization reaction. The organic peroxide is not particularly limited as long as it has a 10-hour half-life temperature of 40°C or higher, and any organic peroxide known in the art can be used. Specific examples of organic peroxides include ketone peroxides, peroxyketals, hydroperoxides, dialkyl peroxides, diacyl peroxides, peroxy esters, and peroxydicarbonates. These organic peroxides may be used alone or in combination of two or more.

[0034] By selecting an organic peroxide with a high activation temperature, the pot life of the sheet-type insulating varnish 1 (i.e., the pot life of the sheet-type insulating varnish 1) can be improved. From the viewpoint of ensuring a pot life of the sheet-type insulating varnish 1 suitable for coil impregnation treatment, it is preferable that the 10-hour half-life temperature of the organic peroxide is 80°C or higher. Furthermore, in order to efficiently proceed with the curing of the sheet-type insulating varnish 1, it is preferable that the 10-hour half-life temperature of the organic peroxide is equal to or lower than the set temperature of the curing oven when curing the sheet-type insulating varnish 1.

[0035] Specific examples of organic peroxides having such a 10-hour half-life temperature include 1,1-di(t-butylperoxy)cyclohexane, 1,1-di(t-hexylperoxy)cyclohexane, 1,1-di(t-hexylperoxy)-3,3,5-trimethylcyclohexane, 1,1-di(t-butylperoxy)-2-methylcyclohexane, 2,2-di(4,4-di-(butylperoxy)cyclohexyl)propane, n-butyl 4,4-di-(t-butylperoxy)valerate, 2,2-di-(t-butylperoxy)butane, t-hexylperoxyisopropyl monocarbonate, t-butylperoxymaleic acid, t-butylperoxy-3,5,5-trimethylhexanoic acid, t-butylperoxylauric acid, t-butylperoxyisopropyl monocarbonate, t-butylperoxybenzoate, t-butylperoxyacetate, t-butylperoxyisopropyl monocarbonate, t-butylperoxybenzoate, t-butylperoxyacetate, t-butylperoxyisopropyl monocarbonate, t-butylperoxybenzoate, t-butylperoxyacetate, t-butylperoxyisopropyl monocarbonate, t-butylperoxybenzoate, t-butylperoxyacetate, t-butylperoxyisopropyl monocarbonate, t-butylperoxybenzoate, t-butylperoxyacetate, t-butylperoxybenzo ... Examples of the peroxyl groups include xyl peroxybenzoate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, t-butylperoxy 2-ethylhexyl monocarbonate, di(2-t-butylperoxyisopropyl)benzene, dicumyl peroxide, di-t-hexyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, di-t-hexyl peroxide, t-butylcumyl peroxide, di-t-butyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexyne-3, p-menthane hydroperoxide, t-butylperoxyallyl monocarbonate, methyl ethyl ketone peroxide, 1,1,3,3-tetramethylbutyl hydroperoxide, t-butyl hydroperoxide, cumin hydroperoxide, and diisopropylbenzene hydroperoxide. These may be used alone or in combination of two or more.

[0036] The amount of organic peroxide is not particularly limited, but is usually 0.1 to 10 parts by mass, more preferably 0.5 to 5 parts by mass, based on 100 parts by mass of polyester resin, which is a thermosetting resin. If the amount of organic peroxide is less than 0.1 parts by mass, the crosslink density may be low and curing may be insufficient. On the other hand, if the amount of organic peroxide is more than 10 parts by mass, the usable time of the sheet-type insulating varnish 1 tends to be significantly shortened.

[0037] In addition, the thermosetting resin composition may contain a curing accelerator as necessary. The curing accelerator is not particularly limited, and a known one may be appropriately selected according to the type of thermosetting resin. Specific examples of the curing accelerator include tertiary amines, imidazoles, and amine adducts. From the viewpoint of the storage stability, curing property, and cured resin properties of the sheet-type insulating varnish 1, a curing accelerator that is inactive at 60° C. or less is more preferable.

[0038] The amount of the curing accelerator is usually 0.01 to 10 parts by mass, more preferably 0.02 to 5.0 parts by mass, based on 100 parts by mass of the total thermosetting resin. If the amount of the curing accelerator is less than 0.01 parts by mass, the effect of accelerating the curing reaction is poor, and if it is more than 10 parts by mass, the usable time tends to be shortened.

[0039] In addition, the thermosetting resin composition may contain a film-forming agent as necessary to improve film-forming properties such as film thickness uniformity and surface smoothness. A thermoplastic resin having a weight average molecular weight of 10,000 to 100,000 is used as the film-forming agent. The amount of the thermoplastic resin is 1 to 50 parts by mass per 100 parts by mass of the first thermosetting resin and the second thermosetting resin. The thermoplastic resin is not particularly limited, and a known thermoplastic resin can be appropriately selected according to the type of thermosetting resin. Specific examples of the thermoplastic resin include, for example, phenoxy resin and saturated polyester resin. These film-forming agents may be used alone or in combination of two or more kinds.

[0040] When the weight average molecular weight of the thermoplastic resin is less than 10,000, the film-forming property is not improved, and when it is more than 100,000, the dissolution and dispersion in the liquid second thermosetting resin is poor, and a slurry cannot be prepared. The amount of the film-forming agent is usually 1 to 50 parts by mass, more preferably 5 to 45 parts by mass, per 100 parts by mass of the thermosetting resin in total, from the viewpoint of curing acceleration and cured resin properties. When the film-forming agent is less than 1 part by mass, the effect of improving the film-forming property is poor, and when it is more than 50 parts by mass, the dissolution and dispersion in the liquid second thermosetting resin is poor, and a slurry cannot be prepared.

[0041] In addition, the thermosetting resin composition may contain a tackifier as necessary to improve the surface adhesion of the sheet-type insulating varnish 1. The tackifier is not particularly limited as long as it has a weight-average molecular weight of 10,000 to 200,000, and a known tackifier may be appropriately selected according to the type of thermosetting resin. Specific examples of the tackifier include terpene resins, rosin resins, natural rubber, styrene elastomers, polyvinyl acetal resins, polyvinyl formal resins, and polyvinyl butyral resins. These tackifiers may be used alone or in combination of two or more.

[0042] When the weight average molecular weight of the tackifier is less than 10,000, the adhesion is not improved, and when it is more than 200,000, the solubility and dispersibility in the liquid second thermosetting resin is poor, and a slurry cannot be prepared. The amount of the tackifier is usually 1 to 20 parts by mass, more preferably 2 to 10 parts by mass, per 100 parts by mass of the thermosetting resin in total, from the viewpoint of curing acceleration and cured resin properties. When the amount of the tackifier is less than 1 part by mass, the effect of improving the surface adhesion is poor, and when it is more than 20 parts by mass, the solubility and dispersibility in the liquid second thermosetting resin is poor, and a slurry cannot be prepared.

[0043] The thermosetting resin composition may contain an adhesion promoter from the viewpoint of improving the adhesive strength at the interface between the thermosetting resin and the inorganic filler, or at the interface between the sheet-type insulating varnish 1 and the member to be insulated. The adhesion promoter is not particularly limited, and a known adhesion promoter may be appropriately selected according to the type of thermosetting resin or inorganic filler.

[0044] Specific examples of adhesion promoters include silane coupling agents such as γ-glycidoxypropyltrimethoxysilane, N-β(aminoethyl)γ-aminopropyltriethoxysilane, N-phenyl-γ-aminopropyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane, etc. These adhesion promoters may be used alone or in combination of two or more kinds. The amount of adhesion promoter may be appropriately set according to the type of thermosetting resin or adhesion promoter, and is usually preferably 0.01 to 5 parts by mass per 100 parts by mass of thermosetting resin.

[0045] Furthermore, when the surface of the components to be insulated is highly uneven and the varnish layer has high thermal fluidity, the thermosetting resin composition cannot fill the gaps between the components to be insulated and voids are formed partially. However, by expanding the thermally expandable microcapsules 3 by heating, the varnish layer thickens, eliminating the voids and reliably filling the gaps between the components. In the case of coils, the varnish is pressed against the varnish layer, so that it flows when heated and penetrates into the coil by capillary action, thereby bonding the coils together. By bonding (adhering) and eliminating the voids, electronic devices and rotating electrical machines with high mechanical strength, cooling performance and insulation performance can be provided.

[0046] The thermally expandable microcapsules 3 are not particularly limited, and may be any microcapsules having a structure in which a thermal expansion agent such as a low-boiling point hydrocarbon is wrapped in a thermoplastic polymer shell made of a thermoplastic resin such as vinylidene chloride resin and acrylic resin having gas barrier properties, and the capsules may expand as the thermoplastic resin of the shell softens and the volume of the thermal expansion agent increases when heated. The surface of the thermally expandable microcapsules 3 may be coated with an inactive inorganic powder such as calcium carbonate, talc, titanium oxide, etc. For example, microparticles that expand when heated may be commercially available microspheres. These thermally expandable microcapsules 3 may be used alone or in a mixture of two or more types.

[0047] The sheet-type insulating varnish 1 is used as interphase insulation by being pasted or inserted into the gap between components to be insulated (for example, between a coil and an iron core). For this reason, it is preferable that the maximum particle size of the thermally expandable microcapsules 3 is smaller than the dimension of the gap, and the average particle size is smaller than 0.5 times the dimension of the gap. For example, when the actual dimension of the gap is 10 μm to 100 μm including the tolerance, thermally expandable microcapsules 3 with a maximum particle size of 10 μm or less and an average particle size of 5 μm or less are selected. Furthermore, since the sheet-type insulating varnish 1 is semi-cured or uncured, it flows when heated and penetrates into the recesses on the surface of the component to be insulated and into the gaps between the components to be insulated. In order to efficiently penetrate, a latent curing agent that is inactive at 60°C or less is used to minimize curing during flow. If the thermally expandable microcapsules 3 foam during the flow of the varnish, it will hinder penetration into the recesses and gaps. Therefore, it is more preferable that the foaming start temperature of the thermally expandable microcapsules 3 is 60°C or higher, and is lower than the reaction start temperature of the latent curing agent + 20°C in order to suppress the increase in viscosity during flow, promote the foaming of the thermally expandable microcapsules 3, and prevent the foam size after curing from becoming excessively large. When the curing accelerator lowers the reaction initiation temperature of the latent curing agent, it is preferable to set the temperature at or below the reaction initiation temperature + 20°C. In order for the sheet-type insulating varnish 1 to bond the components to be insulated, eliminate remaining voids, and reliably fill the gaps between the components, it is necessary to link flow, foaming, and hardening by heating. In other words, it is desirable to determine the heating conditions such that the thermally expandable microcapsules 3 do not foam during flow, foam after flow is complete, and hardening begins after foaming, by raising the temperature or increasing it in stages.

[0048] The amount of the thermally expandable microcapsules 3 is not particularly limited, but if the expansion ratio is too high, the strength and heat resistance of the sheet-type insulating varnish 1 after curing will be significantly reduced, so it is desirable to adjust the amount so that the unevenness of the surface of the member to be insulated and the gaps between the members can be reliably filled. Since the expansion ratio of the thermally expandable microcapsules 3 varies depending on the type and heating temperature, it is difficult to limit the amount of the thermally expandable microcapsules 3 to be blended. From the viewpoint of uniformly mixing the resin composition, the amount is usually 1 part by mass or more and 100 parts by mass or less per 100 parts by mass of the thermosetting resin, and from the viewpoint of ensuring the thermal fluidity of the varnish layer, it is more preferably 90 parts by mass or less. If the amount is less than 1 part by mass, the thickness of the sheet-type insulating varnish 1 is insufficient due to the expansion of the thermally expandable microcapsules 3, and the gaps between the members cannot be reliably filled, and if the amount exceeds 100 parts by mass, the thermal fluidity of the varnish is poor and the coil cannot be fixed. In addition, an organic foaming agent may be used in combination as necessary. Examples of the organic foaming agent include inorganic foaming agents such as ammonium carbonate, ammonium borohydride, ammonium hydrogen carbonate, ammonium nitrite, and azides, azo compounds such as azobisisobutyronitrile, fluorinated alkanes such as trichloromonofluoromethane, semicarbazide compounds such as p-toluenesulfonylsemicarbazide, hydrazine compounds such as paratoluenesulfonylhydrazide, triazole compounds such as 5-morpholyl-1,2,3,4-thiatriazole, and N-nitroso compounds such as N,N'-dinitrosoterephthalamide.

[0049] In addition, the thermosetting resin composition may contain a filler from the viewpoint of improving thermal conductivity and mechanical strength, thickening the sheet-type insulating varnish 1, etc. The filler is not particularly limited, and a known filler may be appropriately selected according to the purpose. The filler may be surface-treated with a silane-based coupling agent, a titanate-based coupling agent, etc., or may not be surface-treated.

[0050] Specific examples of inorganic fillers include crystalline silica, fused silica, alumina, talc, clay, calcium carbonate, calcium silicate, titanium dioxide, silicon nitride, aluminum hydroxide, aluminum nitride, boron nitride, glass, barium sulfate, magnesia, beryllium oxide, mica, magnesium oxide, etc. The shape of the filler is preferably crushed or spherical, but may also be subspherical, scaly, fibrous, milled fiber, whisker, etc. These fillers may be used alone or in combination of two or more.

[0051] In addition, resin-based fillers such as thermoplastic resins, rubber components, and various oligomers may be added to improve the crack resistance and impact resistance of the cured sheet-type insulating varnish 1. Specific examples of thermoplastic resins include butyral resins, polyvinyl acetal resins, polyamide resins, aromatic polyester resins, phenoxy resins, MBS resins (methyl methacrylate-butadiene-styrene copolymers), ABS resins (acrylonitrile-butadiene-styrene copolymers), and acrylic resins, which can be modified with silicone oils, silicone resins, silicone rubbers, fluororubbers, and the like. In addition, various plastic powders, various engineering plastic powders, and the like may be added.

[0052] The amount of the filler may be any amount that can uniformly mix the thermosetting resin composition, and is usually 70% by volume or less relative to the total amount of the thermosetting resin composition, and more preferably 65% ​​by volume or less in consideration of the workability of mixing. If the amount of the filler is greater than 70% by volume, it will not be possible to mix it uniformly with the resin composition, and the reproducibility of the characteristics of the sheet-type insulating varnish 1 will tend not to be obtained. In addition, when the sheet-type insulating varnish 1 is used by folding it, it is necessary to increase its flexibility, so that 50% by volume or less is more preferable. Furthermore, if there is no need to increase the thermal conductivity of the sheet-type insulating varnish 1 or form a thick varnish layer, it is also possible not to mix a filler into the thermosetting resin composition.

[0053] The sheet-type insulating varnish 1 is pasted or inserted into the gap between components to be insulated (for example, between a coil and an iron core) and used as interphase insulation. For this reason, it is preferable that the maximum particle size of the filler is smaller than the size of the gap, and the average particle size is less than 0.5 times the size of the gap. For example, if the actual size of the gap is 10 μm to 100 μm including the tolerance, a filler with a maximum particle size of 10 μm or less and an average particle size of 5 μm or less is selected.

[0054] Furthermore, the thermosetting resin composition may also contain anti-settling agents or dispersants that suppress the settling of solid powders such as fillers in the resin, anti-foaming agents that prevent the generation of voids, anti-blocking agents or slippage improvers such as polymer beads that prevent blocking between particles of the sheet-type insulating varnish 1, paint adhesion promoters, antioxidants, flame retardants, colorants, thickeners, viscosity reducers, surfactants, etc.

[0055] As described above, the sheet-type insulating varnish of embodiment 1 contains a first thermosetting resin that is solid at room temperature, a second thermosetting resin that is liquid at room temperature, thermally expandable microcapsules having a foaming initiation temperature of 60°C or higher, a latent curing agent that is inactive at temperatures below 60°C, and, if necessary, a filler. Therefore, when the sheet-type insulating varnish of embodiment 1 is heated, the thermosetting resin flows and penetrates into the fine gaps in the components to be insulated, reliably filling these gaps, and after hardening, it has excellent insulation properties, mechanical strength, and heat dissipation properties.

[0056] Embodiment 2 In the second embodiment, a method for producing a sheet-type insulating varnish using the thermosetting resin composition according to the first embodiment will be described with reference to the flow chart of FIG. The sheet-type insulating varnish produced by this method for producing a sheet-type insulating varnish is obtained by forming the thermosetting resin composition described in embodiment 1 in an uncured or semi-cured state into a sheet having a thickness of 1 μm to 500 μm.

[0057] The method for producing the sheet-type insulating varnish includes a first step (slurry preparation step) of preparing a slurry of a thermosetting resin composition, and a second step (application and drying step) of applying the slurry to a release film or release paper and drying it. In the first step (slurry preparation step), a diluent is added to the thermosetting resin composition according to embodiment 1 to achieve a predetermined mixture viscosity, and the mixture is stirred and mixed with a stirrer until the thermally expandable microcapsules 3 and filler 4 are uniformly dispersed without settling.

[0058] The slurry contains at least a first thermosetting resin that is solid at room temperature, a second thermosetting resin that is liquid at room temperature, a latent curing agent that is inactive at 60° C. or less, thermally expandable microcapsules 3 that have a maximum particle size smaller than the size of the gap, an average particle size smaller than 0.5 times the size of the gap, and a foaming start temperature of 60° C. or more, and a diluent. The slurry contains 10 to 90 parts by mass of the first thermosetting resin per 100 parts by mass of the thermosetting resin in total, and the thermally expandable microcapsules 3 are mixed in an amount of 1 to 100 parts by mass per 100 parts by mass of the thermosetting resin in total.

[0059] The diluent that dissolves the thermosetting resin is volatilized or evaporated after the coating is completed, and disappears almost completely. The diluent is not particularly limited, and any known diluent can be appropriately selected according to the types of thermosetting resin, thermally expandable microcapsules, filler, etc. used. Specific examples of the diluent include toluene, methyl ethyl ketone, etc. These solvents may be used alone or in combination of two or more kinds. The amount of the solvent to be added is not particularly limited as long as the mixture has a viscosity that allows kneading, and is usually 20 parts by mass to 200 parts by mass per 100 parts by mass of the thermosetting resin.

[0060] Next, in the second step (coating and drying step), the slurry is coated on a release film or release paper using a sheet coater to a film thickness 1.1 to 2.0 times the size of the gap, and then dried in a drying oven to produce a sheet-type insulating varnish 1. The coating method is not particularly limited, and may be performed using a coater known in the art. The prepared sheet-type insulating varnish 1 has a thermosetting resin composition in an uncured or semi-cured state, so when the sheets come into contact with each other, they will adhere (block). For this reason, a base material of a release film or release paper is laminated on one surface, and the base material is released before use.

[0061] In the drying oven, the diluent is volatilized at temperatures between 80°C and 160°C. The non-volatile content after drying is 97 parts by mass or more, and more preferably 99 parts by mass or more, relative to 100 parts by mass of the total mass of the sheet-type insulating varnish 1. If it is less than 97 parts by mass, the remaining diluent makes it difficult to release the varnish from a substrate such as a release paper or a release film. The sheet-type insulating varnish 1 may be in an uncured state (A-stage state) in which only the diluent has been evaporated, or may be in a semi-cured state (B-stage state) in which further heating is performed to advance the curing reaction after the diluent has been evaporated. In blending a first thermosetting resin that is solid at room temperature with a second thermosetting resin that is liquid at room temperature, if the type and amount of the second thermosetting resin is large, the uncured state may be highly viscous, making it difficult to release from a substrate such as a release film. In such cases, the reaction may be accelerated slightly by heating to reduce the viscousness and bring the varnish into a semi-cured state, making it possible to release the varnish. If it is desired to reduce the thermal fluidity of the sheet-type insulating varnish 1 when it is mounted, the fluidity can be controlled by bringing the varnish into a semi-cured state.

[0062] Here, the method for producing the sheet-type insulating varnish will be explained in detail with reference to the flow chart of FIG. The method for producing a sheet-type insulating varnish to be placed in the gap between components to be insulated includes a first step (slurry preparation step) (S01) and a second step (application and drying step) (S02). In the first step (S01), a thermosetting resin composition containing a first thermosetting resin that is solid at room temperature, a second thermosetting resin that is liquid at room temperature, a latent curing agent that is inactive at 60°C or less, and thermally expandable microcapsules 3 whose maximum particle size is smaller than the dimension of the gap, whose average particle size is smaller than 0.5 times the dimension of the gap, and whose foaming start temperature is 60°C or more, in which the first thermosetting resin is 10 to 90 parts by mass per 100 parts by mass of the first thermosetting resin and the second thermosetting resin, and the thermally expandable microcapsules 3 are 1 to 100% by mass per 100 parts by mass of the first thermosetting resin and the second thermosetting resin, is stirred and mixed with an organic solvent for dilution to prepare a slurry of the thermosetting resin composition.

[0063] In the second step (S02), the slurry is applied to a release film or release paper to a thickness that is 1.1 to 2.0 times the size of the gap, and is dried so that the film thickness has a compressibility of 10% or more when a pressure of 25 MPa is applied at room temperature.

[0064] In the second step (S02), the diluent is volatilized by drying at a temperature of 80° C. to 160° C., and the non-volatile content per 100 parts by weight of the total weight of the sheet-type insulating varnish 1 after drying can be 97 parts by weight or more. Furthermore, after the second step (S02), heating can be further carried out to promote the curing reaction, so that the sheet-type insulating varnish 1 can be brought into a semi-cured state.

[0065] As described above, the sheet-type insulating varnish produced by the sheet-type insulating varnish manufacturing method of embodiment 2 has a thermosetting resin that flows when heated, penetrating into the fine gaps in the components to be insulated, reliably filling these gaps, and has excellent properties in terms of insulation, mechanical strength, and heat dissipation after hardening.

[0066] Embodiment 3 In the third embodiment, the characteristics of the sheet-type insulating varnish will be described. The sheet-type insulating varnish 1 preferably has high surface smoothness and flexibility. In order to ensure good adhesion to the component to be insulated and to prevent an air gap from occurring between the cured sheet-type insulating varnish 1 and the component to be insulated, the in-plane distribution of the film thickness of the sheet-type insulating varnish 1 is set to within ±30% of the average value.

[0067] Furthermore, the sheet-type insulating varnish 1 has the flexibility to not crack even when bent 180 degrees at room temperature. If drying proceeds due to excessive heating, the diluent evaporates and the resin hardening reaction proceeds, which may cause the flexibility to be lost. In this case, since the sheet-type insulating varnish does not have the flexibility to conform to the surface shape of the components, cracks may occur when the sheet-type insulating varnish is placed between the components. Alternatively, the sheet-type insulating varnish may not adhere or bond to the components even after being heated and hardened.

[0068] Furthermore, if the sheet-type insulating varnish 1 is too thick, the internal stress increases, and cracks may occur when the sheet-type insulating varnish 1 is bent 180 degrees. The thickness of the sheet-type insulating varnish 1 is preferably 1 μm to 500 μm, and more preferably 5 μm to 300 μm in order to completely fill the gaps between the components to be insulated. If the thickness is less than 1 μm, it is difficult to form a sheet-type insulating varnish without pinholes, and if the thickness exceeds 500 μm, there is a high possibility that cracks will occur during a 180-degree bending test.

[0069] The thickness of the sheet-type insulating varnish 1 is 1.1 times or more the dimension of the gap between the members to be insulated, and is usually set to 1.1 to 2.0 times, more preferably 1.3 to 1.7 times. Specifically, when the dimension obtained by subtracting the thickness of the base material from the dimension of the gap is 100 μm, the thickness of the sheet-type insulating varnish 1 is preferably 110 μm to 200 μm, more preferably 130 μm to 170 μm. When the thickness is less than 110 μm, the heated sheet-type insulating varnish 1 does not sufficiently fill the fine details of the gap, and when the thickness exceeds 200 μm, the members of the electronic device cannot be fixed together with fixing screws, or gaps are generated between the slots during molding of the stator of the rotating electric machine, making it impossible to mold it into a ring shape, and so on, which may deteriorate the ease of assembly.

[0070] The sheet-type insulating varnish 1 has a compressibility such that the film thickness (total thickness) is reduced by 10% or more at room temperature under a pressure of 25 MPa. Considering the dimensional tolerance of the gaps between members, it is more preferable that the film is compressed by 20% or more. Since the sheet-type insulating varnish 1 has a non-volatile content of 97 parts by mass (%) or more, it undergoes a volumetric shrinkage of 3% to 10% when completely cured. In addition, depending on the type, the base material of the sheet-type insulating varnish 1 is hardly compressed at a pressure of 25 MPa, so the film thickness of the sheet-type insulating varnish 1 must be 10% or more larger than the dimension obtained by subtracting the thickness of the base material from the dimension of the gap. If the film thickness of the sheet-type insulating varnish 1 is compressed by less than 10% at a pressure of 25 MPa at room temperature, even if the gap is filled when the sheet-type insulating varnish 1 is placed, small gaps may occur due to cure shrinkage.

[0071] In addition, when the sheet-type insulating varnish 1 is to be applied to a member in advance, it is preferable that the varnish has surface tackiness (tackiness) at room temperature. On the other hand, when application to a member in advance would deteriorate workability, the surface tackiness can be eliminated while maintaining flexibility and film thickness compressibility by using the above-mentioned blending ratio and drying conditions. As an indicator of surface non-stickiness, it is assumed that the tape will not stick even when pressed against an insulating material at a pressure of 2 MPa at 40°C. If the tape adheres under these conditions, the surface stickiness may increase depending on the working environment temperature (25-35°C), resulting in poor workability.

[0072] Sheet-type insulating varnish 1 must have the flexibility to be compressed at room temperature, and must also flow when heated, penetrating into the fine details between components (such as the uneven shapes of coils and iron cores). To obtain these characteristics, the drying state of the sheet-type insulating varnish 1 is important. Flexibility can be judged simply by whether or not cracks occur when bent at 180°C. A method for more quantitatively determining these flexibility and fluidity characteristics is to evaluate the elastic modulus through viscoelasticity measurements.

[0073] As a specific example of viscoelasticity measurement, the storage shear modulus (G') of sheet-type insulating varnish 1 is 1.0 x 103 Pa to 5.0 x 104 Pa at room temperature and decreases with increasing temperature, reaching a minimum value of 10 Pa to 2.0 x 103 Pa at 80°C to 150°C. Sheet-type insulating varnish 1 that does not satisfy the above values ​​does not obtain the required compressibility when pressurized, and does not obtain the ability to penetrate into fine spaces between components.

[0074] In addition, if the minimum value of the storage shear modulus is less than 80°C, the reaction proceeds when left at room temperature, and flexibility is likely to decrease. On the other hand, if the minimum value is 150°C or higher, the heating temperature required for complete curing becomes high, which may deteriorate the substrate. From the viewpoint of maintaining the shape of the sheet-type insulating varnish 1 and expressing fluidity at the heating temperature, it is more preferable that the storage shear modulus at room temperature is 3.0×103 Pa to 3.0×104 Pa, and the minimum value of the storage shear modulus at 80°C to 150°C is 1.0×102 Pa to 5.0×102 Pa, which is one-tenth or less of the value at room temperature. Furthermore, the storage shear modulus at 180°C or higher is saturated at 1.0×105 Pa or higher due to the influence of curing.

[0075] The loss modulus (G") of the sheet-type insulating varnish 1 is 1.0 x 103 Pa to 5.0 x 104 Pa at room temperature and decreases as the temperature rises, reaching a minimum of 10 Pa to 2.0 x 103 Pa at 80°C to 150°C. The loss tangent (tan δ) has a maximum value of 1.0 to 3.5 at 80°C to 150°C. Sheet-type insulating varnish 1 whose loss modulus and loss tangent do not satisfy the above values ​​does not obtain the required compressibility when pressurized, and does not obtain the ability to penetrate into fine parts between components.

[0076] In addition, if the minimum value of the loss modulus or the maximum value of the loss tangent is less than 80°C, the reaction proceeds when left at room temperature, and flexibility is likely to decrease. On the other hand, if they are 150°C or higher, the heating temperature required for complete curing becomes high, which may cause deterioration of the substrate. From the viewpoint of maintaining the sheet-type insulating varnish 1 and expressing fluidity at the heating temperature, it is more preferable that the loss modulus at room temperature is 3.0×103 Pa to 3.0×104 Pa, and the minimum value of the loss modulus at 80°C to 150°C is 1.0×102 Pa to 1.0×103 Pa, which is one-fifth or less of the value at room temperature. The loss modulus at 180°C or higher saturates at 5.0×103 Pa or higher due to the influence of curing, and the loss tangent saturates at 0.2 or less.

[0077] The flexibility and fluidity properties of the sheet-type insulating varnish 1 can also be evaluated by its complex viscosity. The complex viscosity at room temperature is 6.0×102 Pa·s to 1.0×104 Pa·s, and decreases with increasing temperature, reaching its lowest value of 5.0×102 Pa·s or less at 80°C to 150°C.

[0078] A sheet-type insulating varnish 1 that does not satisfy these values ​​will not achieve the required compression ratio when pressurized, and will not be able to penetrate into the fine spaces between components. Furthermore, from the viewpoint of maintaining the shape of the sheet-type insulating varnish 1 and expressing fluidity at heating temperatures, it is more preferable that the complex viscosity at room temperature is 1.0×103 Pa·s to 5.0×103 Pa·s, and that the minimum value of the complex viscosity at 80°C to 150°C is 1 Pa·s to 5.0×102 Pa·s, which is one-tenth or less of the value at room temperature. The complex viscosity at 180°C or higher saturates at 1.0×104 Pa·s or higher due to the effects of curing.

[0079] The sheet-type insulating varnish 1 is placed in the gap between the components to be insulated, and then heat-cured in a curing process. Specifically, the sheet-type insulating varnish 1 is placed in advance on one component (heat-generating component, circuit board, housing, coil, insulating paper, insulating film, iron core, etc.), and is then pressure-bonded and fixed to the other component (same as above). If the sheet-type insulating varnish 1 does not have a sticky surface, it may be attached with double-sided tape or the like to prevent it from falling off.

[0080] As explained in Fig. 2, the sheet-type insulating varnish 1 is efficiently compressed to a predetermined thickness by pressure at room temperature, and flows when heated during hardening, penetrating into the fine spaces between the components. The varnish layer then thickens due to foaming of the thermally expandable microcapsules 3, eliminating the air layer and reliably filling the gaps between the components to be insulated, thereby insulating and bonding them together. Therefore, since it is necessary to continuously proceed with the flow of the varnish, the foaming of the thermally expandable microcapsules 3, and the hardening, the heating temperature may be set to be increased stepwise from the flow temperature (below the foaming start temperature of the thermally expandable microcapsules 3) to the foaming temperature (foaming start temperature of the thermally expandable microcapsules 3 to the reaction start temperature of the latent hardener + 20°C). Note that the hardening temperature is above the reaction start temperature of the latent hardener.

[0081] When the sheet-type insulating varnish is heated, the thermally expandable microcapsules 3 foam and form voids inside. Since the voids reduce the insulating properties and mechanical strength of the cured product, the void size is an average of 30 μm or less to maintain the insulating properties, and an average of 20 μm or less is more preferable to obtain uniform insulating properties and stable mechanical strength. If the pore size exceeds an average of 30 μm, the insulating properties deteriorate after the varnish is cured, such as a decrease in the dielectric breakdown voltage and the occurrence of partial discharge, and the mechanical strength decreases, deteriorating the vibration resistance of the product. The thermally expandable microcapsules 3 can obtain hollow microparticles by controlling the increase in volume (expansion) by changing the internal gas pressure according to the heating temperature and heating time. It is necessary to set the heating temperature and heating time so that the pore size of the hollow microparticles is 30 μm or less on average, and the heating temperature (foaming temperature) is preferably 60°C to 200°C, but must be 20°C or less higher than the reaction start temperature of the latent curing agent. When the reaction initiation temperature of the latent curing agent is lowered by the curing accelerator, it is preferable to set the reaction initiation temperature + 20°C or less. In order to suppress foaming variation, 80°C to 180°C is more preferable. If it is less than 60°C, the flow of the varnish is hindered, and if it exceeds 200°C, the varnish hardens first, foaming is not performed, and the pore size cannot be controlled. The heating time (foaming time) is not particularly limited as long as it is a time that can control the pore size to an average of 30 μm or less, and from the viewpoint of suppressing foaming variation, 30 seconds to 1 hour is preferable. The thickness increase after curing of the sheet-type insulating varnish 1 is not particularly limited as long as the pore size of the hollow particles of the thermally expandable microcapsules 3 is 30 μm or less on average and the gaps between the components to be insulated can be reliably filled, but it is preferable that the film thickness after curing increases by 10% or more compared to the initial film thickness. If the increase is less than 10%, the fine gaps cannot be filled and air layers remain.

[0082] The sheet-type insulating varnish 1 is placed in the gaps between the components to be insulated (e.g., coils, iron cores, etc.), and then heated and cured in a curing process. The heating temperature in the curing process varies depending on the types of curing agent and curing accelerator, but is set to a heating temperature and time that will not deteriorate the components to be insulated. Specifically, the heating temperature is preferably 100°C to 200°C, and more preferably 130°C to 190°C. The heating time is preferably 1 minute to 6 hours, and more preferably 3 minutes to 2 hours.

[0083] If the heating temperature is less than 100°C or the heating time is less than 1 minute, the curing is insufficient and the material cannot be bonded or fixed to the component. At relatively low temperatures of 100°C to 170°C, the material is unlikely to deteriorate even if it is heated for more than 6 hours, but if it is heated for more than 6 hours at 170°C or higher, or if it is heated at a high temperature of 200°C or higher, the material may deteriorate. Since the sheet-type insulating varnish 1 contains almost no solvent, it can be cured by induction heating or electric heating, which simplifies the curing process.

[0084] In addition, the sheet-type insulating varnish 1 preferably has an adhesive strength of 10 N / m or more after curing to integrate the members to be insulated and improve vibration resistance, and more preferably has an adhesive strength of 20 N / m or more to suppress characteristic variations in vibration resistance. If the adhesive strength is less than 10 N / m, sufficient vibration resistance cannot be obtained, and the long-term reliability of the device decreases.

[0085] Sheet-type insulating varnish 1 having the above-mentioned properties is efficiently compressed to a specified thickness when pressurized at room temperature, and flows when heated during hardening, penetrating into the fine spaces between components. The varnish layer then thickens as the expandable microcapsules foam, eliminating air spaces and reliably filling the gaps between the components to be insulated, thereby insulating and bonding them together.

[0086] Embodiment 4 In the fourth embodiment, an example in which the sheet-type insulating varnish of the first embodiment is applied to an electric device will be described with reference to FIG. In the fourth embodiment, a power supply device is assumed as an example of an electric device for explanation. Examples of the power supply device include a switching type DC-DC converter, an AC-DC converter, and the like. In the fourth embodiment, electronic devices are taken as an example of the application of the sheet-type insulating varnish, but the application is not limited to this and can be applied to electrical devices in general.

[0087] 4 includes a substrate 10 on which electronic components 9 are mounted, and a housing 11 to which the substrate 10 is fixed. The electronic components 9 include heat-generating components such as field effect transistors (MOSFETs (Metal Oxide Semiconductor Field Effect Transistors)), diodes, and capacitors. The electronic component 9 is fixed to the board 10 by a fixing screw 12 , and the board 10 is fixed to the housing 11 by a fixing screw 13 .

[0088] A filled through hole 14 is formed in the substrate 10, a sheet-type insulating varnish 1C is disposed in the gap between the electronic component 9 and the substrate 10, and a sheet-type insulating varnish 1D is disposed in the gap between the substrate 10 and the housing 11. That is, in the case of the power supply device 15, the gaps between the components in which the sheet-type insulating varnishes 1C and 1D are disposed are the gap between the electronic component 9 (heat-generating component) and the substrate 10, and the gap between the substrate 10 and the housing 11. In order to distinguish them from the sheet-type insulating varnish 1 of the first embodiment, they are referred to as sheet-type insulating varnishes 1C and 1D.

[0089] In the gap between the electronic component 9 and the substrate 10, a sheet-type insulating varnish 1C with a thickness 1.2 times the dimension of the gap is applied to the substrate 10 side, and then the electronic component 9 is fixed to the substrate 10 with fixing screws 12 and heated to 130°C to 200°C to cause the sheet-type insulating varnish 1C to flow, foam, and harden. When insulating the gap between the substrate 10 and the housing 11, a sheet-type insulating varnish 1D with a thickness 1.2 times the dimension of the gap (indicated as G1 in the figure) is applied to the side of the housing 11, and then the substrate 10 is fixed to the housing 11 with fixing screws 13 and heated to 130°C to 200°C to cause the sheet-type insulating varnish 1D to flow, foam, and harden.

[0090] Sheet-type insulating varnishes 1C and 1D are efficiently compressed to a specified thickness when pressurized at room temperature, and when heated during hardening, they flow and penetrate into the fine spaces between components.The varnish layer then thickens as the expandable microcapsules foam, eliminating air spaces and reliably filling the gaps between the components to be insulated, thereby insulating and bonding them together. If the heating temperature is set to a constant temperature and the air layer is not sufficiently removed, the heating temperature may be increased stepwise from the flow temperature (below the foaming start temperature of the thermally expandable microcapsules 3) to the foaming temperature (foaming start temperature of the expandable microcapsules to reaction start temperature of the latent hardener + 20°C) in order to continuously and efficiently proceed with the flow of the varnish, the foaming of the thermally expandable microcapsules 3, and the hardening. Note that the hardening temperature is equal to or higher than the reaction start temperature of the latent hardener. Through this curing treatment, the electronic component 9 is fixed to the substrate 10 by the sheet-type insulating varnish 1C. Furthermore, the substrate 10 and the housing 11 are insulated by the sheet-type insulating varnish 1D, and the substrate 10 is fixed to the housing 11. From the viewpoint of workability, it is preferable that the sheet-type insulating varnishes 1C and 1D before curing have surface tackiness.

[0091] Sheet-type insulating varnishes 1C and 1D are made so that they have the flexibility to be compressed at room temperature before hardening, flow when heated to penetrate into the fine spaces between components, and then the varnish layer thickens due to foaming of the expandable microcapsules, eliminating the air layer and reliably filling the gaps. Specifically, sheet-type insulating varnishes 1C and 1D have the flexibility to not break even when bent 180 degrees, and have the permeability to the fine spaces between components by setting the storage shear modulus, loss modulus, loss tangent, and complex viscosity within the predetermined ranges explained in the third embodiment.

[0092] Therefore, the sheet-type insulating varnishes 1C and 1D penetrate into the fine gaps between the electronic components 9 and the substrate 10 and the fine gaps between the substrate 10 and the housing 11 by heating during the curing process, and then the varnish layer thickens due to the expansion of the thermally expandable microcapsules 3, thereby eliminating the air layer and reliably filling the gaps. Therefore, the power supply device 15 using the sheet-type insulating varnishes 1C and 1D is less susceptible to insulation deterioration, and heat generated from the electronic components 9 during operation is efficiently dissipated to the substrate 10. In addition, since the sheet-type insulating varnishes 1C and 1D do not contain a solvent, they can be cured not only by a general-purpose heating furnace but also by induction heating and electric heating. Furthermore, since there is little energy loss during the curing process, the curing time is short, and the manufacturing process of the power supply device is simplified.

[0093] On the other hand, when liquid insulating materials such as insulating coating agents and potting agents are used, the insulating material flows through the gaps between components, making it difficult to completely fill the gaps. In addition, liquid insulating materials contain solvents, which cause a large amount of organic components to volatilize during the curing process after application, resulting in hygiene and odor problems. In addition to the resin curing reaction during the curing process, organic components that are not involved in the curing reaction also volatilize, resulting in large energy losses in the heating furnace and longer curing times. As a result, CO2 emissions increase, creating environmental problems.

[0094] According to the fourth embodiment, by disposing sheet-type insulating varnishes 1C and 1D in the gap between the electronic component 9 and the substrate 10, and in the gap between the substrate 10 and the housing 11, respectively, it is possible to improve the insulation reliability, heat dissipation performance, and vibration resistance, and to realize a miniaturized and high-output power supply device 15. In FIG. 4, sheet-type insulating varnishes 1C and 1D are placed in both the gap between the electronic component 9 and the substrate 10 and the gap between the substrate 10 and the housing 11, but sheet-type insulating varnish 1C (1D) may also be placed in only one of the gaps.

[0095] As described above, in the fourth embodiment, the sheet-type insulating varnish of the first embodiment is applied to an electric device. Therefore, according to the fourth embodiment, it is possible to provide electrical equipment to which a sheet-type insulating varnish is applied, in which the thermosetting resin flows when heated and penetrates into the fine gaps in the components to be insulated, reliably filling these gaps, and which has excellent properties in terms of insulation, mechanical strength, and heat dissipation after hardening.

[0096] Embodiment 5. In the fifth embodiment, an example in which the sheet-type insulating varnish of the first embodiment is applied to a rotating electrical machine will be described with reference to Figs. 5 to 8.

[0097] First, a description will be given of the structure of a stator of a rotating electric machine such as an electric motor, a generator, a compressor, etc. Fig. 5 is a perspective view of the stator of a rotating electric machine, and Fig. 6 is a cross-sectional view. 5 and 6, the rotating electric machine is equipped with a stator 20 including a stator coil 21 and an annular stator core 22. A predetermined number of slots 24 are provided in the circumferential direction between teeth 23 of the stator core 22, and the stator coil 21 is housed in the slots 24.

[0098] Next, application of the sheet-type insulating varnish to a stator 20 of a rotating electrical machine will be described with reference to Fig. 7 and Fig. 8. Note that to distinguish it from the sheet-type insulating varnish 1 of the first embodiment, it is referred to as a sheet-type insulating varnish 1E. As shown in FIG. 7, in the gap between the stator core 5 (the inner wall of the slot 24) and the stator coil 21, a sheet-type insulating varnish 1E is placed. Insulating paper 25 or insulating film may be placed in the gap between the inner wall of the slot 24 and the stator coil 21. In this case, sheet-type insulating varnish 1E is placed on the coil side surface of the insulating paper 25, as shown in Fig. 8. Note that sheet-type insulating varnish 1E may also be placed on both sides of the insulating paper 25. That is, insulating paper 25 may be placed between the inner wall of slot 24 and sheet-type insulating varnish 1E, or insulating paper 25 and sheet-type insulating varnish 1E may be placed between the inner wall of slot 24 and sheet-type insulating varnish 1E so that insulating paper 25 is sandwiched between sheet-type insulating varnish 1E. In the case of a rotating electric machine, the gap between the components to be insulated is the gap between the stator core 22 and the stator coil 21, or the gap between the insulating paper 25 and the stator coil 21, or the gap between the stator core 22 and the insulating paper 25. Note that insulating tape may be attached to the stator coil 21.

[0099] In a slot 24 where insulating paper 25 is not placed, when the actual dimension of the gap between the stator core 22 and the stator coil 21 is 30 μm to 150 μm including tolerance, the thermally expandable microcapsules 3 and filler 4 are selected to have a maximum particle size of 30 μm or less and an average particle size of 15 μm or less. In addition, in the slot 24 in which the insulating paper 25 is arranged, when the actual dimension of the gap minus the thickness of the insulating paper 25 is 10 μm to 100 μm including tolerance, the thermally expandable microcapsules and filler selected have a maximum particle size of 10 μm or less and an average particle size of 5 μm or less.

[0100] In the manufacturing process of a rotating electric machine, the sheet-type insulating varnish 1E is applied to the stator core 22 or the insulating paper 25, the stator coil 21 is then arranged, and the sheet-type insulating varnish 1E is compressed and fixed by forming the stator core 22 into a ring shape. At this time, if the film thickness of the sheet-type insulating varnish 1E is too large, gaps will occur between the slots 24 during forming, and it will not be possible to form it into a ring shape.

[0101] Furthermore, since the thickness of the sheet-type insulating varnish 1E is set to be larger than the dimension of the gap between the stator core 22 and the stator coil 21, the thickness must be reduced by the pressure applied when the stator core 22 is molded into an annular shape. If the thickness is compressed by less than 10% at a pressure of 25 MPa at room temperature, gaps will be generated between the slots 24 during molding, and the varnish cannot be molded into an annular shape. For this reason, the thickness of the sheet-type insulating varnish 1E is set to be 1.1 to 2.0 times, more preferably 1.3 to 1.7 times, the dimension of the gap between the stator core 22 and the stator coil 21, and is compressed by 10% or more, more preferably 20% or more, at a pressure of 25 MPa at room temperature.

[0102] Furthermore, in the case of the stator 20 of a rotating electrical machine, if a sheet-type insulating varnish 1E having surface tackiness is applied in advance to the stator core 22 or the insulating paper 25, the workability deteriorates when inserting the stator coil 21. For this reason, the sheet-type insulating varnish 1E is selected to be one that does not have surface tackiness at room temperature while retaining flexibility and compressibility.

[0103] When heated during the curing process, the sheet-type insulating varnish 1E penetrates into the gaps between the stator core 22 or insulating paper 25 and the stator coil 21, and into the fine gaps in the stator coil 21, and then the varnish layer is thickened by the thermally expandable microcapsules 3, thereby eliminating the air layer and reliably filling the gaps. The sheet-type insulating varnish 1E is efficiently compressed to a specified thickness when pressurized at room temperature, and when heated during hardening, it flows and penetrates into the fine spaces between the components.The varnish layer then thickens as the thermally expandable microcapsules 3 foam, eliminating air spaces and reliably filling the gaps between the components to be insulated, thereby insulating and bonding them together. If the heating temperature is set to a constant temperature and the air layer is not sufficiently removed, the heating temperature may be increased stepwise from the flow temperature (below the foaming start temperature of the thermally expandable microcapsules 3) to the foaming temperature (foaming start temperature of the thermally expandable microcapsules 3 to the reaction start temperature of the latent hardener + 20°C) in order to continuously and efficiently proceed with the flow of the varnish, the foaming of the thermally expandable microcapsules 3, and the hardening. Note that the hardening temperature is equal to or higher than the reaction start temperature of the latent hardener. As a result of this hardening treatment, the rotating electric machine using the sheet-type insulating varnish 1E has high insulating performance and is less susceptible to insulation deterioration in the stator coil 21. In addition, heat generated from the windings of the stator coil 21 can be efficiently dissipated to the stator core 22.

[0104] Furthermore, since the stator coil 21 can be reliably fixed, mechanical strength is maintained and NVH characteristics are improved. Also, since the sheet-type insulating varnish 1E does not contain a solvent, it can be cured not only in a general-purpose heating furnace but also by induction heating and electric heating. Furthermore, since there is little energy loss during the curing process, the curing time is short, and the manufacturing process of the rotating electric machine is simplified.

[0105] According to embodiment 5, by disposing sheet-type insulating varnish 1E in the gap between the stator core 22 or insulating paper 25 and the stator coil 21, or in the gap between the stator core 22 and the insulating paper 25, it is possible to improve insulation reliability, heat dissipation performance, and vibration resistance, thereby enabling the rotating electric machine to be made smaller and have higher output.

[0106] As described above, in the fifth embodiment, the sheet-type insulating varnish of the first embodiment is applied to a rotating electrical machine. Therefore, according to embodiment 5, a rotating electric device can be provided to which a sheet-type insulating varnish is applied, in which the thermosetting resin flows when heated and penetrates into the fine gaps of the components to be insulated, reliably filling these gaps, and having excellent properties in terms of insulation, mechanical strength, and heat dissipation after hardening.

[0107] Embodiment 6 In the sixth embodiment, examples and comparative examples of sheet-type insulating varnish will be described. The sheet-type insulating varnish of the present application will be described in detail with reference to examples and comparative examples, but the present application is not limited to these. In the examples and comparative examples, the following materials were mixed in the proportions shown in Tables 1 and 2 to prepare thermosetting resin compositions. A diluent was added to each of these thermosetting resin compositions, which were then applied to a release film. The diluent was then evaporated and dried to a non-volatile content of 99% or more to prepare sheet-type insulating varnishes.

[0108] <First solid thermosetting resin> (1-1) Bisphenol A type epoxy resin (epoxy equivalent 1500, softening point 100°C) (1-2) Bisphenol A vinyl ester resin (weight average molecular weight 2000, softening point 80°C)

[0109] <Liquid second thermosetting resin> (2-1) Bisphenol A type epoxy resin (epoxy equivalent: 185) (2-2) Neopentyl glycol dimethacrylate (weight average molecular weight 240)

[0110] <Hardening agent> (3-1) Dicyandiamide (reaction start temperature 160°C) (3-2) 2,5-dimethyl-2,5-di(t-butylperoxy)hexane (10-hour half-life temperature 117.9°C) (3-3) Propyleneamine (reactive at room temperature)

[0111] <Curing accelerator> (4-1) 1-cyanoethyl-2-methylimidazole (reaction start temperature 100°C) (4-2) 1,8-diazabicyclo[5.4.0]undecene-7 (reaction start temperature 100°C)

[0112] <Thermoplastic resin> (5-1) Phenoxy resin (polymerization average molecular weight 150,000) (5-2) Polyester resin (weight average molecular weight 100,000)

[0113] <Thermal expansion microcapsules> (6-1) Maximum particle size 15μm, average particle size 10μm, foaming start temperature 65℃ (6-2) Maximum particle size 30 μm, average particle size 20 μm, foaming start temperature 120°C (6-3) Maximum particle size 100μm, average particle size 50μm, foaming start temperature 180℃ (6-4) Maximum particle size 45μm, average particle size 25μm, foaming start temperature 125℃ (6-5) Maximum particle size 60 μm, average particle size 35 μm, foaming start temperature 185°C (6-6) Maximum particle size 95 μm, average particle size 45 μm, foaming start temperature 50°C (6-7) Maximum particle size 105 μm, average particle size 55 μm, foaming start temperature 120°C

[0114] <Inorganic filler> (7-1) Fused silica (maximum particle size 7 μm, average particle size 2 μm) (7-2) Alumina (maximum particle size 18 μm, average particle size 5 μm) (7-3) Crystalline silica (maximum particle size 130 μm, average particle size 60 μm)

[0115] [Table 1]

[0116] [Table 2]

[0117] As shown in Table 1, the sheet-type insulating varnishes of Examples 1-5 were made according to the raw materials and their compositions described in the above-mentioned Embodiments 1 and 2. On the other hand, as shown in Table 2, the sheet-type insulating varnishes of Comparative Examples 1-7 do not follow the raw materials and their compositions described in the above-mentioned Embodiments 1 and 2, and are not compatible with the sheet-type insulating varnishes of the present application.

[0118] The sheet-type insulating varnishes of Examples 1-5 and Comparative Examples 1-7 were evaluated for surface smoothness, flexibility, compressibility, adhesion, releasability, gelation time, storage shear modulus, loss modulus, loss tangent, and complex viscosity. The cured products of the sheet-type insulating varnishes were also evaluated for adhesive strength, dielectric strength, film thickness increase rate, and pore size of the thermally expandable microcapsules. Furthermore, a stator was manufactured, and the gap state between the coil and the iron core and the coil adhesion state were observed.

[0119] Next, the contents of each evaluation will be explained. Surface smoothness was judged based on whether the in-plane distribution of the thickness of the sheet-type insulating varnish was within ±30% of the average value (◯: within ±30%, ×: over ±30%). Measurements of flexibility and compressibility were performed twice, once immediately after the sheet-type insulating varnish was made and once after storing it at 40°C for 30 days, in order to confirm the usable life of the sheet-type insulating varnish. Flexibility was judged based on the presence or absence of cracks or chips that occurred when the sheet-type insulating varnish was bent 180 degrees at 25°C (◯: no cracks or chips, ×: present). The compressibility of the sheet-type insulating varnish was calculated from the reduction in thickness of the sheet-type insulating varnish placed on a rolled steel plate and subjected to a pressure of 25 MPa at 25°C. The evaluation of the compressibility was judged based on whether the compressibility was 10% or more (◯: 10% or more, ×: less than 10%).

[0120] Adhesion was evaluated by placing the sheet-type insulating varnish on a rolled steel plate and pressing it with a pressure of 2 MPa at 40°C to see whether it adhered or not, immediately after preparation and after storing it at 40°C for 30 days. Note that it is not possible to say which is better, since there are cases where adhesion is preferable and cases where it is not, depending on the application of the sheet-type insulating varnish. However, it is not desirable for adhesion to change between immediately after preparation and after 30 days, so this point was evaluated.

[0121] Additionally, to investigate the effect on the coating of the enamelled wire, the occurrence of crazing was confirmed. An enamelled wire (φ1.0 mm) with a polyesterimide / polyamideimide coating was stretched 5% and then bent into a U-shape to prepare a test specimen, and a sheet-type insulating varnish was applied to the surface of the coating at room temperature and peeled off after 5 minutes. If the sheet-type insulating varnish was not sticky (tacky) and would not stick, it was fixed with a clip and brought into contact. After peeling, an optical microscope observation and a pinhole test were performed to evaluate the occurrence of crazing.

[0122] The pinhole test was conducted in accordance with JISC3003, in which a test piece of the specified length (approximately 5 m) was immersed in saline solution, and the liquid was used as the positive electrode and the test piece as the negative electrode, and a direct current voltage of 12 V was applied for 1 minute to check the number of pinholes that occurred. In addition, the test pieces that were cured at 150°C for 1 hour after application were also observed with an optical microscope to see if there were any cracks or pinholes on the coating surface. If there were no cracks or pinholes and no drop in the dielectric breakdown voltage, it was determined that there was no crazing, and if there were cracks or pinholes and a drop in the dielectric breakdown voltage, it was determined that there was crazing (○: no crazing, ×: crazing).

[0123] The gelation time was measured by taking a sample of the thermosetting resin composition of the sheet-type insulating varnish and measuring the gelation time at 150°C using a hot plate method. The softening point was measured by taking a sheet made of the thermosetting resin composition and measuring it in accordance with JISC2161 "Testing method for powder coatings for electrical insulation". The storage shear modulus, loss modulus, loss tangent, complex viscosity, and minimum complex viscosity were measured by dynamic viscoelasticity evaluation using a sheet-type insulating varnish with a film thickness of 100 μm to 300 μm and heating it from room temperature at a heating rate of 5°C / min using a parallel plate jig.

[0124] Test pieces for measuring the properties of the cured product of sheet-type insulating varnish were prepared by heating the test pieces in a heating furnace from room temperature to 150°C in 10 minutes, and then curing at 150°C for 1 hour, in order to sequentially proceed through the flow, foaming, and curing of the varnish.

[0125] Adhesive strength was evaluated by preparing adhesive test pieces and using a tensile tester. Adhesive strength was evaluated by preparing adhesive test pieces and using a tensile tester. Adhesive test pieces were prepared by pressing sheet-type insulating varnish onto an electromagnetic steel plate with a surface treated with acetone degreasing and curing it. The tensile test was performed at 25°C, with a peel angle of 180 degrees and a pulling speed of 10 mm / min, and was evaluated according to the following criteria (○: adhesive strength of 10 N / m or more, ×: adhesive strength less than 10 N / m).

[0126] The dielectric strength voltage was measured by attaching a sheet-type insulating varnish to one side of a steel plate, heating it from room temperature to 150°C over 10 minutes, and curing it at 150°C for 1 hour.The dielectric breakdown voltage was then measured using a dielectric breakdown tester in oil at a constant voltage increase of 0.5 kV / sec, and the dielectric breakdown voltage was evaluated according to the following criteria (○: dielectric breakdown voltage 8 kV or more, ×: dielectric breakdown voltage 8 kV or less).

[0127] The film thickness increase rate was calculated by dividing the film thickness after curing by the film thickness before curing to confirm whether or not the film thickness increased after curing. In addition, the pore size of the thermally expandable microcapsules after curing was measured by cross-sectional observation and judged (◯: average particle size 30 μm or less, ×: over 30 μm).

[0128] To verify the use of sheet-type insulating varnish in a rotating electric machine, a stator was fabricated by changing the coil in Figure 6 from a rectangular shape to a round wire with a diameter of 1.5 mm so that the gap between the coil and the iron core would be larger. A sheet-type insulating varnish with a film thickness of 120 μm was inserted into the gap of 100 μm between the coil and the iron core and pressed, and then the temperature was raised from room temperature to 150°C in 10 minutes and cured at 150°C for 1 hour. After curing, the cross section was observed to confirm whether there was an air layer between the iron core and the coil (◯: no air layer, ×: air layer present). Furthermore, the coil was removed to confirm the adhesion state between the coils (◯: completely adhered, ×: not adhered).

[0129] The evaluation results of the sheet-type insulating varnishes of Examples 1-5 are shown in Table 3, and the evaluation results of the sheet-type insulating varnishes of Comparative Examples 1-7 are shown in Table 4.

[0130] [Table 3]

[0131] [Table 4]

[0132] All of the sheet-type insulating varnishes according to Examples 1-5 have excellent flexibility and releasability immediately after preparation and after 30 days, and have a compression rate of 20% or more. They do not cause crazing on enameled wires. In addition, their storage shear modulus at 25°C is within the range of 1.0×10 Pa to 5.0×10 Pa, with the minimum value being within the range of 10 Pa to 2.0×10 Pa at 80°C to 150°C. In addition, their loss modulus at 25°C is within the range of 1.0×10 Pa to 5.0×10 Pa, with the minimum value being within the range of 10 Pa to 2.0×10 Pa at 80°C to 150°C.

[0133] Moreover, the maximum value of the loss tangent is within the range of 1.0 to 3.5 at 80°C to 150°C. Furthermore, the complex viscosity at 25°C is within the range of 6.0 x 102 Pa·s to 1.0 x 104 Pa·s, and the minimum value is 500 Pa·s or less at 80°C to 150°C. From the above evaluation results, it is clear that the sheet-type insulating varnish of Example 1-5 is compressed to a predetermined thickness by pressure at room temperature, and is able to penetrate into fine parts between components by heating during curing.

[0134] Moreover, the sheet-type insulating varnishes according to Examples 1-5 all have an adhesive strength of 20 MPa or more at 25°C, and can firmly bond and fix the components to be insulated. Furthermore, the insulation voltage resistance after curing is high, and the insulation reliability is excellent. Furthermore, since there is no change in flexibility and compressibility after 30 days of storage at 40°C, the reaction progresses slowly at room temperature, and the usable life is long. The thermally expandable microcapsules are foamed after curing, and the pore size is 30 μm or less, and the varnish film thickness is also increased. Furthermore, in the verification using a stator, there is no gap between the coil and the iron core, and the coil is completely fixed.

[0135] Comparative Example 1 has a similar formulation to Example 1, but does not contain thermally expandable microcapsules. Therefore, the varnish layer does not thicken after hardening, and the gap between the coil and the iron core is not filled, leaving an air layer.

[0136] Comparative Example 2 has a similar formulation to Example 2 and contains 105 parts by mass of thermally expandable microcapsules (6-1) per 100 parts by mass of thermosetting resin, so that a sheet-type insulating varnish with a smooth surface cannot be obtained. In addition, because the viscosity of the varnish layer when heated is high, it does not flow into the gaps between the coils, and the coils cannot be fixed.

[0137] Comparative Example 3 is similar to the formulation of Example 3, contains a curing agent (3-3) that is reactive at room temperature, and the foaming start temperature of the thermally expandable microcapsules (6-3) is 180°C, which is significantly higher than the reaction start temperature of the curing agent. For this reason, the reaction proceeds when left stationary at room temperature, and the physical properties change over time, which causes problems with the usable time. After 30 days, flexibility and adhesion are lost, and the compression rate becomes 0%. In addition, since the fluidity during heat curing is low, penetration into small gaps is not obtained, and the adhesive strength with the components is poor. Furthermore, since the curing proceeds at room temperature, there is no flow of the varnish layer, the thermally expandable microcapsules do not foam, and the film thickness of the sheet-type insulating varnish does not increase at all, so the gap between the coil and the iron core cannot be filled, and the coil cannot be fixed. In addition, cracks and peeling occur when the product is bent during use, which deteriorates the workability.

[0138] Comparative Example 4 is similar to the formulation of Example 4, and contains thermally expandable microcapsules (6-4) with an average particle size of 25 μm and a foaming start temperature of 125° C. The raw materials constituting the composition are problem-free, and the characteristics of the sheet-type insulating varnish and the verification with the stator are also good, but the pore size of the thermally expandable microcapsules that foamed after curing was large at an average of 35 μm, which not only reduced the insulation, but also reduced the adhesion of the coil due to insufficient strength of the cured product. Note that by reviewing the curing conditions such as the heating rate and curing temperature, it may be possible to reduce the pore size and improve these issues.

[0139] Comparative Example 5 is similar to the formulation of Example 5, and uses thermally expandable microcapsules (6-5) whose foaming start temperature is 25°C higher than the reaction start temperature of the latent hardener (3-1) and crystalline silica (7-3) with a maximum particle size of 130 μm and an average particle size of 60 μm as an inorganic filler. Since it contains an inorganic filler with a large particle size, the surface smoothness deteriorated when a sheet-type insulating varnish with a film thickness of 120 μm was produced. When heated, the varnish flows into the gaps in the coil and can fix the coil, but since the curing reaction proceeds first, the thermally expandable microcapsules do not foam and the film thickness of the sheet-type insulating varnish does not increase at all, so the air layer existing in the gap between the coil and the iron core could not be filled. In addition, in the verification of a stator with a gap between the coil and the iron core of 100 μm, a gap occurred between the teeth because the maximum particle size (130 μm) of the inorganic filler was larger than the gap (100 μm), and a stator could not be produced.

[0140] Comparative Example 6 is similar to the formulation of Example 5, and contains thermally expandable microcapsules (6-6) with an average particle size of 60 μm at a foaming start temperature of 50° C. and 73 volume % of fused silica (7-1) as an inorganic filler. Because it contains a large amount of inorganic filler, the sheet-type insulating varnish has poor smoothness, low toughness, no flexibility or adhesion, and a compression rate of 0%. In addition, because it contains thermally expandable microcapsules with a low foaming start temperature (50° C.), foaming progresses at the start of heating, hindering the fluidity of the varnish, making it impossible to fix the coil.

[0141] Comparative Example 7 is similar to the formulation of Example 2, and uses thermally expandable microcapsules (6-7) with a maximum particle size of 105 μm, an average particle size of 55 μm, and a foaming start temperature of 120° C. Since it contains thermally expandable microcapsules with a large maximum particle size, when a sheet-type insulating varnish with a film thickness of 120 μm was produced, the surface smoothness decreased. Since the particle size of the thermally expandable microcapsules is large, the pore size becomes large to an average of 50 μm when foamed after curing, and in addition to the decrease in insulation, the adhesion of the coil is decreased due to the insufficient strength of the cured product. In addition, in the verification with the stator, since it contains thermally expandable microcapsules with a maximum particle size larger than the dimension of the gap (100 μm) and an average particle size larger than 0.5 times the dimension of the gap (50 μm), when it is hardened after being inserted into the gap between the coil and the iron core and pressed, the foaming of the thermally expandable microcapsules is insufficient, and the air layer existing in the gap between the coil and the iron core cannot be filled.

[0142] As described above, in Examples 1 to 5, all evaluation items were good, whereas in Comparative Examples 1 to 7, some evaluation items were poor.

[0143] Although the present application describes various exemplary embodiments and examples, the various features, aspects, and functions described in one or more embodiments are not limited to application to a particular embodiment, but may be applied to the embodiments alone or in various combinations. Therefore, countless modifications not exemplified are assumed within the scope of the technology disclosed in this application, including, for example, modifying, adding, or omitting at least one component, and further, extracting at least one component and combining it with a component of another embodiment. [Industrial Applicability]

[0144] The sheet-type insulating varnish of the present application is a thermosetting resin that flows when heated, penetrating into the fine gaps in the components to be insulated, reliably filling these gaps, and after curing has excellent insulation properties, mechanical strength, and heat dissipation properties, making it suitable for a wide range of electrical equipment and rotating electrical machines. [Explanation of symbols]

[0145] 1a, 1b, 1C, 1D, 1E sheet-type insulating varnish, 2 resin component, 3 thermally expandable microcapsule, 4 filler, 7 air layer, 8 foamed thermally expandable microcapsule, 9 electronic component, 10 substrate, 11 housing, 12, 13 fixing screws, 14 filled through-hole, 15 power device, 20 stator, 21 stator coil, 22 stator core, 23 teeth, 24 slot, 25 insulating paper.

Claims

1. A sheet-type insulating varnish that is placed in the gap between components to be insulated, the thermosetting resin composition includes a first thermosetting resin that is solid at room temperature, a second thermosetting resin that is liquid at room temperature, a latent curing agent that is reactively inactive at 60° C. or less, and thermally expandable microcapsules that have a maximum particle size smaller than the size of the gap, an average particle size smaller than 0.5 times the size of the gap, and a foaming start temperature of 60° C. or more, and the thermosetting resin composition includes 10 to 90 parts by mass of the first thermosetting resin relative to a total of 100 parts by mass of the first thermosetting resin and the second thermosetting resin, and is formed into a sheet in an uncured or semi-cured state; In the case where a curing accelerator is further included and the reaction initiation temperature of the latent curing agent is lowered by the curing accelerator, the foaming initiation temperature of the thermally expandable microcapsule is 60° C. or higher and is 20° C. higher than the reaction initiation temperature of the curing accelerator, The amount of the thermally expandable microcapsules blended in the sheet-type insulating varnish is 1 to 100% by mass based on the total amount of the first thermosetting resin and the second thermosetting resin.

2. 2. The sheet-type insulating varnish according to claim 1, wherein the average size of voids formed in the foamed thermally expandable microcapsules after curing is 30 μm or less.

3. 3. The sheet-type insulating varnish according to claim 1, which has a compressibility such that a film thickness of the sheet-type insulating varnish is reduced by 10% or more when a pressure of 25 MPa is applied thereto at room temperature.

4. The sheet-type insulating varnish according to claim 1 , wherein the first thermosetting resin and the second thermosetting resin include at least one of an epoxy resin, a phenolic resin, and an unsaturated polyester resin.

5. 5. The sheet-type insulating varnish according to claim 1, wherein the latent hardener is any one of a boron trifluoride-amine complex, dicyandiamide, and an organic acid hydrazide.

6. 6. The sheet-type insulating varnish according to claim 1, further comprising an inorganic or resin-based filler, the filler amounting to 70% by volume or less based on the total amount of the thermosetting resin composition.

7. The electronic device includes a substrate on which electronic components are mounted and a housing to which the substrate is fixed, An electrical device comprising the sheet-type insulating varnish according to any one of claims 1 to 6, which is disposed in either or both of a gap between the electronic component and the substrate and a gap between the substrate and the housing.

8. 8. The electric device according to claim 7, wherein the sheet-type insulating varnish is heated to cause the thermosetting resin composition to flow, foam, and harden.

9. The stator coil is housed in the slots of the stator core. A rotating electric machine comprising the sheet-type insulating varnish according to any one of claims 1 to 6, which is disposed in a gap between an inner wall of the slot and the stator coil.

10. An insulating paper is disposed between the inner wall of the slot and the sheet-type insulating varnish; 10. The rotating electric machine according to claim 9, wherein an insulating paper and a sheet-type insulating varnish are disposed between the inner wall of the slot and the sheet-type insulating varnish such that the insulating paper is sandwiched by the sheet-type insulating varnish.

11. 11. The rotating electric machine according to claim 9, wherein the sheet-type insulating varnish is heated, so that the thermosetting resin composition flows, foams, and hardens.

12. A method for producing a sheet-type insulating varnish to be placed in a gap between components to be insulated, comprising the steps of: The present invention includes a first thermosetting resin that is solid at room temperature, a second thermosetting resin that is liquid at room temperature, a latent curing agent that is inactive at 60° C. or less, and thermally expandable microcapsules having a maximum particle size smaller than the size of the gap, an average particle size smaller than 0.5 times the size of the gap, and a foaming start temperature of 60° C. or more, The first thermosetting resin is 10 parts by mass to 90 parts by mass per 100 parts by mass of the total of the first thermosetting resin and the second thermosetting resin; A first step of preparing a slurry of a thermosetting resin composition by stirring and mixing a thermosetting resin composition, in which the thermally expandable microcapsules are 1 to 100% by mass relative to 100 parts by mass of the total of the first thermosetting resin and the second thermosetting resin, and an organic solvent for dilution; The slurry is applied to a release film or release paper to a thickness of 1.1 to 2.0 times the size of the gap; A method for producing a sheet-type insulating varnish comprising: a second step of drying the varnish so that the film thickness has a compression rate of 10% or more when a pressure of 25 MPa is applied at room temperature.

13. The method for producing a sheet-type insulating varnish according to claim 12, wherein in the second step, the diluent is volatilized by drying at a temperature condition of 80°C to 160°C, and the non-volatile content of the sheet-type insulating varnish after drying is 97 parts by mass or more per 100 parts by weight of the total mass of the sheet-type insulating varnish.

14. The method for producing a sheet-type insulating varnish according to claim 12 or 13, further comprising, after the second step, heating for promoting a curing reaction, bringing the sheet-type insulating varnish into a semi-cured state.

Citation Information

Patent Citations

  • Thermally expandable sheetlike adhesive composition

    JP2007106963A

  • Thermally expandable adhesive sheet and manufacturing method thereof

    JP2013104044A

  • Expansion sheet for rotary electric machine, stator for rotary electric machine using the same, and manufacturing method of the stator for rotary electric machine

    JP2013236468A

  • Sheet type insulation varnish and method for manufacturing the same, electric apparatus and rotary electric machine

    JP2021070748A

  • Adhesive sheet

    WO2016163514A1